Utilizing Path Analysis to Examine the Influence of Internship Experiences and Work Information Mastery on VHS Students’ Work Readiness - Sari, Darti Purnama; Kamil, Insan; Dewi, Ifti Luthviana; Setiawan, Oki; Manalu, Haposan Vincentius; Adriani, Siti; Sasniati, Popi (Universitas Negeri Padang, 2025)
This research investigates how internship experience and work information mastery influence vocational students’ work readiness, with work motivation acting as a mediating factor. The research population comprises all twelfth-grade students majoring in Mechanical Engineering at a Vocational High School in Yogyakarta, Indonesia, totaling 310 individuals. The maximum sample of 170 students was determined using Issac & Michael’s formula. The sample was selected through purposive sampling techniques, and data were collected using questionnaires, tests, and documentation. Descriptive statistical analysis was employed to summarize the characteristics of each variable, while hypothesis testing was conducted using path analysis in an ex-post facto research design. The results indicate that the proposed research model satisfies both validity and reliability tests, thus validating the suitability of the model. The findings reveal: (1) a significant indirect effect between internship experience and work readiness mediated by work motivation (t = 3.787, sig. 0.000), and (2) a significant indirect effect of work information mastery and work readiness through work motivation (t = 2.907, sig. 0.003). The results of the study indicate that internship experience and mastery of information through work motivation influence students' job readiness. The implication of this research is that schools need to increase collaboration with industry and strengthen the role of teachers, parents, and the Community Empowerment Agency (CEA) in providing information and guidance about the world of work, so that vocational high school graduates are better prepared and more easily accepted into the workforce.